Naming as a tool of constructing territorial identity (on the example of choosing the name for the new terminal оf the perm airport) - Nazukina, M.V. (Perm Federal Research Centre Journal, 2018)
The article observes the peculiarities of naming practices as an aspect of territorial identity. The characteristic of names as a tool of identity politics is given. It is determined that naming is an important way of constructing and maintaining the identity. Two main functional roles of naming are singled out. The first is the construction of new traditions or the reconstruction of the old ones. The second is the representation of the community, the formation through giving the name of the image outside. The characteristic of this tool of identity policy is given on the example of studying the Contest for the choice of the name of the terminal of the Perm airport, which was held in October-November 2017. The choice of the object of the study is due to the symbolic role of the airport («face», «gates» to the city), so it can characterize the state of territorial identity. The analysis of the Contest showed the competition of geographical (Perm, Bolshoye Savino) and personal names (named after S.P. Diaghilev, P.A. Solovyov, A.G. Soldatov, S.A. Belov, I.I. Lyubimov, «Stroganov»). It was determined that the discourse strategies of the presentation of the nominees were linked to the achievements of people, their contribution to the development of the place. The evaluation of the Contest in the context of the specifics of the Perm regional identity is given. It is proved that the choice of the former name «Bolshoye Savino» demonstrates the Permian traditionalism and the craving for something familiar as opposed to changes.